N-Acetylaspartate reductions in brain injury: impact on post-injury neuroenergetics, lipid synthesis, and protein acetylation - Moffett, John R.; Arun, Peethambaran; Ariyannur, Prasanth S.; Namboodiri, Aryan M. (Frontiers in Neuroenergetics, 2013)
N-Acetylaspartate (NAA) is employed as a non-invasive marker for neuronal health using proton magnetic resonance spectroscopy (MRS). This utility is afforded by the fact that NAA is one of the most concentrated brain metabolites and that it produces the largest peak in MRS scans of the healthy human brain. NAA levels in the brain are reduced proportionately to the degree of tissue damage after traumatic brain injury (TBI) and the reductions parallel the reductions in ATP levels. Because NAA is the most concentrated acetylated metabolite in the brain, we have hypothesized that NAA acts in part as an extensive reservoir of acetate for acetyl coenzyme A synthesis. Therefore, the loss of NAA after TBI impairs acetyl coenzyme A dependent functions including energy derivation, lipid synthesis and protein acetylation reactions in distinct ways in different cell populations. The enzymes involved in synthesizing and metabolizing NAA are predominantly expressed in neurons and oligodendrocytes respectively, and therefore some proportion of NAA must be transferred between cell types before the acetate can be liberated, converted to acetyl coenzyme A and utilized. Studies have indicated that glucose metabolism in neurons is reduced, but that acetate metabolism in astrocytes is increased following TBI, possibly reflecting an increased role for non-glucose energy sources in response to injury. NAA can provide additional acetate for intercellular metabolite trafficking to maintain acetyl CoA levels after injury. Here we explore changes in NAA, acetate and acetyl coenzyme A metabolism in response to brain injury.